Conceptual and theoretical approaches to corporate social responsibility, entrepreneurial orientation, and financial performance - Paiva, Inna Sousa; Carvalho, Luísa Cagica, 1970- (Advances in business strategy and competitive advantage., 2020)
"This book explores new trends in corporate social responsibility, entrepreneurial orientation, and financial performance"--